2018
DOI: 10.1002/lsm.22820
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of removing solar lentigines in Asians using a novel dual‐wavelength and dual‐pulse width picosecond laser

Abstract: To the best of our knowledge, this is the first study using a picosecond Nd:YAG laser 532-nm for removing solar lentigines in darker skin types that includes histological evaluation. Although there are many options to treat solar lentigines, our results suggest that picosecond laser with preferable endpoint determination can be a safer and more effective treatment over conventional treatments in Asian patients. Lasers Surg. Med. 50:851-858, 2018. © 2018 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(104 citation statements)
references
References 28 publications
6
97
0
1
Order By: Relevance
“…The incidence of PIH in lesions was 10.2% which was slightly higher compared with other published literature [18,19]. Although Guss et al [20] reported an incidence of 0.8% of PIH in the removal of 255 lentigines from six patients, and Negishi et al [3] reported an incidence of 4.65% in the treatment of 43 lesions in 20 females, we believe our results still support that the picosecond laser is a safe treatment option for the treatment of solar lentigines. Our laser setting was similar to that of Negishi et al which used parameters of 532-nm, low energy green mode, 750 ps, average fluence 0.35 ± 0.6 J/cm 2 (range 0.2-0.5) spot size 3 or 4 mm with a repetition rate of single or 1 Hz, where our parameters were 532-nm, 750 ps, fluence of 0.2-0.5 J/cm 2 , with a repetition rate of 2 Hz.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The incidence of PIH in lesions was 10.2% which was slightly higher compared with other published literature [18,19]. Although Guss et al [20] reported an incidence of 0.8% of PIH in the removal of 255 lentigines from six patients, and Negishi et al [3] reported an incidence of 4.65% in the treatment of 43 lesions in 20 females, we believe our results still support that the picosecond laser is a safe treatment option for the treatment of solar lentigines. Our laser setting was similar to that of Negishi et al which used parameters of 532-nm, low energy green mode, 750 ps, average fluence 0.35 ± 0.6 J/cm 2 (range 0.2-0.5) spot size 3 or 4 mm with a repetition rate of single or 1 Hz, where our parameters were 532-nm, 750 ps, fluence of 0.2-0.5 J/cm 2 , with a repetition rate of 2 Hz.…”
Section: Discussionsupporting
confidence: 49%
“…The shorter pulse widths in the picosecond domain destroys melanosomes not only through photothermal effect but also through photo‐acoustic effect. Negishi et al further demonstrated this through histological findings of destroyed melanosomes with surrounding structural damage with QS Nd:YAG laser, whereas no obvious surrounding structural damage was observed in picosecond laser treated skin samples . At even shorter pulse duration than picosecond, plasma formation can be a complication.…”
Section: Discussionmentioning
confidence: 98%
“…It more efficiently breaks down melanin while causing less irritation and fewer complications. It has been reported that PS laser is highly efficient against solar lentigines, yielding a treatment response rate of 93.02% with >75% clearance with only a single treatment, whereas the PIH rate was reported to be lower at 4.65% with a demonstration of minimal disruption of the epidermo-dermal junction when compared with traditional QS lasers [6]. Newer laser wavelengths with PS technology, such as 670 nm, allows deeper penetration and even fewer complications to the normal epidermal melanin while causing less irritation to hemoglobin and blood vessels owing to its high melanin-to-hemoglobin ratio ( Fig.…”
Section: Freckles and Solar Lentiginesmentioning
confidence: 99%
“…It can break down the pigment particles into smaller pieces than can traditional quality-switched (QS) lasers, thereby allowing the immune system to more efficiently remove the fractured pigments. Further, it has been histologically proven that QS lasers more easily www.jcosmetmed.org damage the surrounding tissue than PS lasers [6]. Therefore, PS lasers have better treatment margin and efficacy than QS lasers, and are a good therapeutic option for Asian BPDs.…”
Section: Introductionmentioning
confidence: 99%
“…This treatment strategy however is quite challenging because of the high risk of damage to surrounding tissues that can lead to long-lasting and delayed postinflammatory hyperpigmentation. So, proper patient counseling with regard to side effects, and expectations should always be done prior to any laser therapy [45,46].…”
Section: Laser Therapymentioning
confidence: 99%